Revitalisasi Nilai-Nilai Khitbah Didalam Hadis Sebagai Upaya Menjaga Kemuliaan Perempuan (Analisis Hadis Tematik) - Husnul Khatimah (El Nubuwwah Jurnal Studi Hadis, 2023)
The values of khitbah contained in authentic hadith are indeed important to study. Remembering the khitbah here is the process before the consent qabul occurs in marriage. Whereas marriage is a very strong bond and the longest worship in life, therefore as Muslims we must follow the guidance of the Prophet, remembering that Rasulullah SAW is our example. Making the values in this hadith very important, steps must be taken to revitalize these values. One of them is by analyzing several hadiths which explain the terms and conditions of khitbah in Islam. For this study the authors used qualitative methods with thematic study analysis. The author’s object is to discuss the values in the hadith and how to maintain the glory of women. Where the results of this literature research explain that the purpose of the prophet’s hadiths is to glorify women and not even be rigid in providing protection for the rights and obligations of husbands and wives.